DEVELOPING INCLUSIVITY: EMOTIONAL INTELLIGENCE AND NONVERBAL COMMUNICATION (American Journal of Pedagogical and Educational Research, 2025)
Recently, Uzbekistan, a strategically critical country in Central Asia, has started a major reform program with the goal of creating a society that is more inclusive and open. Uzbekistan is on a difficult but determined route toward greater inclusion, one that calls for strong civil society involvement, successful policy execution, and ongoing political will. It bases its claim on recent reports and scholarly assessments. The article examines progress and challenges across various dimensions, including developing emotional intelligence and various ways of nonverbal communication.